Littordial F, a novel phloroglucinol meroterpenoid from the leaves of Psidium littorale. Issue 28 (11th July 2019) - Zhu, Hui-Lin; Hu, Yun-Wei; Qu, Wei; Zhang, Jie; Guo, Er-Yan; Jiang, Xue-Yang; Liu, Wen-Yuan; Feng, Feng; Xu, Jian
Graphical abstract: Highlights: A novel meroterpenoid with an unique 6/8/9/4-tetracyclic nucleus was isolated. The absolute configuration was confirmed by computational 13 C NMR and optical rotation data. Compound1 exhibited potential cytotoxic activities. Abstract: Littordial F (1 ), a novel meroterpenoid with an unique 6/8/9/4-tetracyclic nucleus, was isolated from the leaves of Psidium littorale . The structure of1 was established by spectroscopic data, and its absolute configuration was confirmed by computational 13 C NMR and optical rotation data. Compound1 exhibited potential cytotoxic activities on A549, B16, and HepG-2 cell lines. A plausible biosynthetic pathway for littordial F was proposed.